Effects of carbon disclosure project on financial performance - Della Ramadhana; Windijarto Windijarto (Institute of Computer Science (IOCS), 2023)
Companies that are aware of the environmental crisis will immediately take action to minimize environmental pollution risks and protect their reputation and image by disclosing information. This can reduce financial risks to a certain extent. This study aims to examine the impact of carbon disclosure projects on corporate financial performance. The methodological approach taken in this study used systematic literature research (SLR). Total of 24 articles were obtained that could be used in the systematic literature review . The Carbon Disclosure Project (CDP) can positively impact the company's financial performance in several aspects. The results indicate that environmental disclosure, including carbon disclosure, can attract investor interest, fulfill stakeholder demands, and reduce transaction costs. This can positively impact the company's stock market value, revenue, net income, and equity value. However, the relationship between carbon disclosure and financial performance may vary depending on contextual factors, such as industry, country, and specific disclosure practices.